2008
DOI: 10.1002/jmv.21274
|View full text |Cite
|
Sign up to set email alerts
|

First report on fatal myocarditis associated with adenovirus infection in Cuba

Abstract: Myocarditis is caused frequently by viral infections of the myocardium. In the past, enteroviruses (EV) were considered the most common cause of myocarditis in all age groups. Other viruses that cause myocarditis are adenovirus and influenza viruses. Parvovirus B19 infection is associated sometimes with myocarditis. Members of the Herpesviridae family, cytomegalovirus (CMV), and human herpesvirus 6 (HHV-6) have been associated occasionally with myocarditis. During an atypical outbreak of acute febrile syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Quantification of viral load may help to resolve this problem. Several studies showed that types 1, 2, 3, 5 and 21 are associated with myocarditis in children [16]. Fatal cases of HAdV-3 myocarditis have been reported by Treacy et al [15].…”
Section: Discussionmentioning
confidence: 96%
“…Quantification of viral load may help to resolve this problem. Several studies showed that types 1, 2, 3, 5 and 21 are associated with myocarditis in children [16]. Fatal cases of HAdV-3 myocarditis have been reported by Treacy et al [15].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, in Cuba, an outbreak of febrile syndrome followed by acute cardiac decompensation in infants and young children has been described (13,15). In six of the eight fatal cases, adenoviral DNA was detected in the lungs and myocardium.…”
Section: Case Reportmentioning
confidence: 99%
“…Other viruses that cause myocarditis are adenovirus, influenza, parvovirus B19, members of the Herpesviridae family, cytomegalovirus (CMV), and human herpesvirus 6 (HHV-6) have all been associated occasionally with myocarditis [11]. Viral genomes are frequently detected by polymerase chain reaction enhancement in endomyocardial biopsies of patients with systolic left ventricular dysfunction and this may play a role in the pathogenesis of cardiomyopathy far more frequently [12,13].…”
Section: Discussionmentioning
confidence: 99%